The Effect of Ethnicity and Economy upon Intergenerational Coresidence : Northern Norway during the Last Part of the Nineteenth Century - Jåstad, Hilde Leikny (Journal of Family History, 2011)
This article is part of Hilde L. Jåstad's doctoral thesis. Available in Munin at http://hdl.handle.net/10037/3372 During the last part of the nineteenth century, Finnmark province and the Northern part of Troms experienced a decline in intergenerational coresidence. This article discusses what impact ethnic affiliation and economic activity had on the living arrangements of the elderly, and what contributed to the change. Logistic regression shows that ethnicity played a role, but its effect disappears after controlling for economic activity. Intergenerational coresidence was positively associated with being a married Sámi male with an occupation in farming or combined fishing and farming. As such a person grew older, he was increasingly likely to live separately from an own adult child. This pattern changed towards the end of nineteenth century. By the close of the century, ethnic differences had disappeared, and headship position, irrespective of marital status, was strongly related to coresidence.